The Role of Applying Metagenomic Next-Generation Sequencing (mNGS) in Periprosthetic Joint Infection with Sinus Tract: A Retrospective Study - Yuan X; Wang Q; Ding H; Li H; Fang X; Zhang W; Huang Z (International Journal of General Medicine)
Xuhui Yuan,1– 3,* Qijin Wang,1– 4,* Haiqi Ding,1– 3,* Hongyan Li,1– 3 Xinyu Fang,1– 3 Wenming Zhang,1– 3 Zida Huang1– 3 1Department of Orthopaedic Surgery, the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350005, People’s Republic of China; 2Department of Orthopaedic Surgery, National Regional Medical Center, Binhai Campus of the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350212, People’s Republic of China; 3Fujian Provincial Institute of Orthopedics, the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350005, People’s Republic of China; 4Department of Orthopaedic Surgery, The Affiliated Mindong Hospital of Fujian Medical University, Fuan, 351100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenming Zhang, Department of Orthopaedic Surgery, the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350005, People’s Republic of China, Tel +8613950391800, Email zhangwm0591@fjmu.edu.cn Zida Huang, Department of Orthopaedic Surgery, the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350005, People’s Republic of China, Tel +8618106026516, Email huangzida@163.comBackground: Diagnosing periprosthetic joint infection (PJI), especially with sinus tracts, is challenging using traditional cultures. Metagenomic next-generation sequencing (mNGS) offers a culture-independent diagnostic approach. We evaluated mNGS’s role in diagnosing and guiding treatment for PJI with sinus tracts.Methods: This retrospective analysis included 52 PJI patients (2019– 2024). An mNGS group (n=43; 18 sinus PJI, 25 non-sinus PJI) was compared to a non-mNGS control group (n=9; all sinus PJI, culture-diagnosed). We compared pathogen detection rates. For sinus PJI patients (two-stage revision), 2-year cure rates and antibiotic duration were compared between mNGS-guided and non-mNGS-guided therapy.Results: In sinus PJI cases (n=18), mNGS achieved significantly higher pathogen detection (88.9%, 16/18) versus culture (50.0%, 9/18) (Relative Risk [RR] 1.78; P=0.027). mNGS also detected more polymicrobial infections (38.9%, 7/18) compared to culture (5.6%, 1/18) (RR 7.00; P=0.041). For sinus PJI treatment, mNGS-guided therapy yielded a significantly higher 2-year cure rate (94.4%, 17/18) than non-mNGS therapy (55.6%, 5/9) (Absolute Risk Increase 38.9%; RR 1.70; P=0.03). Mean antibiotic duration was significantly shorter with mNGS guidance (35.62 ± 5.42 vs 47.11 ± 6.53 days; difference 11.49 days; P< 0.01), with a trend towards fewer antibiotic-related complications (11.1% vs 55.6%; P=0.23).Conclusion: mNGS significantly improves pathogen detection, especially polymicrobial infections, in sinus tract PJI. mNGS-guided therapy for sinus PJI is associated with substantially improved cure rates and shorter antibiotic duration, highlighting its utility in guiding targeted anti-infection strategies for these complex cases.Keywords: prosthetic joint infection, metagenomic next-generation sequencing, mNGS, sinus tract, bacteria, diagnosis